The Benefits of Creating an Integrated EU Market for Investment Funds - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
The fast growing EU market for investment funds is still characterised by a continuing relevance of national borders. This papers assesses this market?s degree of integration, the potential benefits from more integration and the obstacles to cross-border sales of funds. The analysis shows that markets of small member countries are particularly isolated since for suppliers of funds the market potential is too small to compensate for the fixed costs of market entry. But also in the big markets foreign funds lack market success. A better integrated European market for investment funds would provide three kinds of benefits: It increases choice of products, it allows to realise economies of scale and it intensifies competition for the benefit of private investors. It is argued that the present characteristics of fund distribution channels are mainly responsible for fragmentation besides regulatory and tax issues.
Keywords: G38; G23; 330; UCITS; investment fund; European integration; Investmentfonds; Internationaler Finanzmarkt; Marktintegration; Skalenertrag; Wettbewerb; EU-Staaten